A surface potential study of ion-uptake by 5,11,17,23-tetra-tert-butyl-25,27-diethoxycarbonyl methyleneoxy-26,28,dihydroxycalix[4]arene and 5,17-(3-nitrobenzylideneamino)-11,23-di-tert-butyl-25,27- diethoxycarbonyl methyleneoxy-26,28-dihydroxycalix[4]arene Langmuir Blodgett (LB) monolayers - F.L. Supian,; T.H. Richardson,; M. Deasy,; F. Kelleher,; J.P. Ward, (Universiti Kebangsaan Malaysia, 2010)
A study of surface pressure - area (Π-A) isotherms, surface potential (ΔV) and effective dipole moment () of two calix[4] arenes, 5,11,17,23-tetra-tert-butyl-25,27-diethoxycarbonyl methyleneoxy-26,28,dihydroxycalix[4]arene (calixarene I) and 5,17-(3-nitrobenzylideneamino)-11,23-di-tert-butyl-25,27-diethoxycarbonyl methyleneoxy-26,28-dihydroxycalix[4] arene (calixarene II) LB films which have the same lower rim but different upper rim has been carried out. This work used a NIMA Surface Potential (S-POT) sensor attached to an LB trough. Space filling model or Corey, Pauling and Koltun (CPK) precision molecular models have been used to estimate the size and the flexibility of both calix[4]arenes, which has been confirmed by X-Ray analysis in one case. The Π-A-isotherms confirmed that both of the calix[4]arenes form a monolayer film and the orientations of the plane of the calix ring are parallel with the air-water interface. The value of limiting area, (Alim) increases as a result of adding Fe3+ salt in the water subphase. For I, the value increases from 1.28 nm2 to 1.44 nm2 while for II, it increases from 1.70 nm2 to 1.86 nm2. ΔV measurements were performed on a water subphase containing Fe3+ salt in the concentration range 0 – 1.25 10–1 mM. ΔV of the compressed monolayer films increased with increasing Fe3+ concentration indicating the presence of Fe3+ salt bound within the calix[4]arenes. Using the ΔV values, the effective dipole moment has been found using the Helmholtz equation.